Case Rounds Redefined: Multidisciplinary Perspectives in Reflective Practice - Megan Bess; Nira Geevargis; June T. Tai (Washington University Journal of Law and Policy, 2024)
This article describes the rounds process used in clinic and externship seminars and considers how adjustments to the structure can address different needs or goals. The authors draw on teaching methods found in similar professional education programs to identify options for faculty facilitating rounds. Ultimately, the authors use externship rounds to highlight lawyering skills, including developing curiosity, withholding judgment, and generating options. The authors posit that rounds facilitate deeper self-reflection and foster a sense of community by encouraging law students to work collaboratively to consider lessons learned in fieldwork. The rounds structure overview can be assigned to students before class and serve as a resource for new faculty. Additionally, the article includes supplementary materials tailored for classroom use.
Keywords: ClinicalLegalEducation; ExternshipRounds; LawyeringSkills; CollaborativeLearning; FacultyResources